(untitled) (Revista de Ciencias de Seguridad y Defensa, 2023)
The article presents, based on statistics and data about Ecuador, the importance of the application and promotion of citizen competencies considered by UNESCO as mandatory in the 21st century, for which it specifically details the critical spirit, social connection, respect for the diversity and ethics of the population influence aspects of the national reality, geopolitics and security of the country. As a methodology, conceptual cartography was used to organize the analyzed information from different sources, generally bibliographic, especially the academic search Google. The results obtained are a contribution to the promotion of these competencies and the starting point for the study of the benefit that these and new citizen competencies can generate to the Ecuadorian State and society.